2011
DOI: 10.1080/15017419.2010.507375
|View full text |Cite
|
Sign up to set email alerts
|

Deaf people's employment and workplaces – similarities and differences in comparison with a reference population

Abstract: This study aims to describe and analyze the characteristics of deaf people in employment and their workplaces in Sweden. A population of 2144 people born 1941Á80 who attended a school for the deaf was compared to 100,000 randomly chosen individuals from the total Swedish population born 1941Á80. Data on these persons consisted of registered information from the year 2005. Results showed that there are differences between the workplaces of people in the deaf and the reference population. For instance, deaf peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In the past 25 years there has been a marked rise in deaf people, in the U.K. and in other developed nations, taking on white collar professional roles and middle and senior management posts in workplaces and organizations where hearing speaking people predominate (Schley et al, 2011;Schroedel & Geyer, 2000). In part this is a result of a rise in educational attainment associated with better access to quality education (Rydberg, Gellerstedt, & Danermark, 2011). Such roles require frequent communicative interaction and a high degree of literacy and consequently sign language interpreters in the workplace have become a more frequently recurring condition.…”
Section: Deaf People In the Workplacementioning
confidence: 99%
“…In the past 25 years there has been a marked rise in deaf people, in the U.K. and in other developed nations, taking on white collar professional roles and middle and senior management posts in workplaces and organizations where hearing speaking people predominate (Schley et al, 2011;Schroedel & Geyer, 2000). In part this is a result of a rise in educational attainment associated with better access to quality education (Rydberg, Gellerstedt, & Danermark, 2011). Such roles require frequent communicative interaction and a high degree of literacy and consequently sign language interpreters in the workplace have become a more frequently recurring condition.…”
Section: Deaf People In the Workplacementioning
confidence: 99%
“…Previous studies have found that people with disabilities face more obstacles to get a job (e.g., [11,21,24,34]) and have lower educational level compared to people without disabilities [39,41]. However, there are also educational and occupational differences found between groups with different disabilities [6,8,10].…”
Section: Which Factors Are Related To Occupational Attainment?mentioning
confidence: 99%
“…Several studies (e.g., [11,21,24,34]) focus on the problems that a certain disability group has on the labor market, without making comparisons between groups with different disabilities. However, in Surveys on Living Conditions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hart et al (2004) put forward that completion of further education improves opportunities to secure meaningful employment. While higher education facilities are available, they are not always accessible, and having higher levels of qualifications does not guarantee a place in the labour market (Rydberg et al, 2011). Individuals with hearing impairment are further disadvantaged due to diverse socio-economic conditions and as a result the greater population of hearing impaired individuals are unable to afford higher education.…”
Section: Discussionmentioning
confidence: 99%
“…Educational levels and severity of hearing loss influence employment and income opportunities in various ways, with the more severe the hearing loss, the less the likelihood of obtaining paid work (Stam, Kostense, Festen & Kramer, 2013;Boutin & Wilson, 2009), whereas higher or tertiary education had a more positive effect on employment (Walter & Dirmyer, 2013;Schley et al, 2011;Rydberg, Gellerstedt & Danermark, 2011). Perkins-Dock et al 2015 (Maja et al, 2011).…”
Section: Employers' Experiences Related To Recruiting and Retaining Imentioning
confidence: 99%